Bismuth Tantalum Oxyhalogen: A Promising Candidate Photocatalyst for Solar Water Splitting. Issue 1 (1st September 2017) - Tao, Xiaoping; Zhao, Yue; Mu, Linchao; Wang, Shengyang; Li, Rengui; Li, Can
Abstract: As wide range of light absorption and suitable redox potentials are prerequisites for photocatalytic water splitting, exploring new semiconductor‐based materials with proper band structures for water splitting still calls for longstanding efforts. In this work, a series of photocatalysts, bismuth tantalum oxyhalide, Bi4 TaO8 X (X = Cl, Br), with valence band and conduction band positions at ≈−0.70 and ≈1.80 eV versus the reversible hydrogen electrode (RHE), respectively, are found to be capable for both water oxidation and reduction under visible light irradiation. Using flux synthetic methods, Bi4 TaO8 X (X = Cl, Br) with microplatelet morphology can be successfully prepared. The photocatalyst based on these materials shows an apparent quantum efficiency as high as 20% at 420 nm for water oxidation. In addition, a Z‐scheme system coupling Bi4 TaO8 Br with Ru/SrTiO3 :Rh is successfully achieved for overall water splitting with a stoichiometric ratio of H2 and O2 evolutions. This work demonstrates a new series of semiconductors Bi4 TaO8 X (X = Cl, Br) with the promising application in the field of solar energy utilization. Abstract : A series of photocatalysts, bismuth tantalum oxyhalides, Bi4 TaO8 X (X = Cl, Br), with the energy band gaps of around 2.5 eV, are explored and found to be capable of both water oxidation and reduction under visible light irradiation. Notably, an apparent quantum efficiency as high as 20% (at 420 nm) for water oxidation is achieved.